Natural Features, Wettability, and Optical Diffraction Patterns on an Elastomeric Replica of a Superhydrophobic Leaf Derived via Soft Lithography - Budlayan, Marco Laurence M. (Archīum Ateneo, 2023)
Surface features of natural materials such as cuticles, shells, and leaves continue to be used as models for creating sophisticated infrastructure, landscape, and microdevice designs. Optical microscopy is the easiest and most accessible tool for examining such surface features and micropatterns. This method, however, fails to probe opaque surfaces like thick skin and leaves since it needs enough light to penetrate the sample. In this work, we demonstrate the feasibility of probing the natural structures of a superhydrophobic leaf using simple optical microscopy by replicating the leaf surface on an elastomer via soft lithography. Optical images of the replica revealed intricate details of features present on the leaf, including the stoma, cuticle boundary, and trichome. Contact angle measurements were also conducted to investigate the wettability of the real leaves and their replicas. Finally, we utilized the fabricated replicas as optical gratings that were observed to generate various diffraction patterns with fluctuating intensities. Our work offers a new perspective on alternative optical microscopy strategies and optical beam tuning using biomimetic, low-cost materials.